Untersuchungen zur Bemessungsgrundlage und zum kassenmäßigen Aufkommen der Steuern vom Umsatz - Alfred Boss (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
In light of the ongoing discussion on the erosion of the tax base in Germany, the relation between value added tax (VAT) revenues and their macroeconomic underpinnings is investigated. Based on a highly disaggregated classification of private consumption and specific government expenditures it could be shown that the relation between VAT revenues and their determinants did not become weaker in the 1990s. Thus it is justified to use traditional methods in forecasting the VAT revenues.
Keywords: H29; 330; value-added tax; estimation; forecasting; Umsatzsteuer; Steuerbemessung; Steueraufkommen; Steuerschätzung; Gesamtwirtschaftliche Nachfrage; Deutschland